2020
DOI: 10.1038/s41524-020-00431-2
|View full text |Cite
|
Sign up to set email alerts
|

Active learning of deep surrogates for PDEs: application to metasurface design

Abstract: Surrogate models for partial differential equations are widely used in the design of metamaterials to rapidly evaluate the behavior of composable components. However, the training cost of accurate surrogates by machine learning can rapidly increase with the number of variables. For photonic-device models, we find that this training becomes especially challenging as design regions grow larger than the optical wavelength. We present an active-learning algorithm that reduces the number of simulations required by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 40 publications
0
54
0
Order By: Relevance
“…To determine how many design variables should be included, consider that an arbitrary lossless and reciprocal four-port admittance matrix has a maximum of ten degrees of freedom. However, due to field averaging arguments, the degrees of freedom are reduced to effective material parameters in electrically-small structures, [22], [23]. The beamformer can be viewed as a lossless, reciprocal, polarization conserving medium supporting a TE wave in the x-z plane.…”
Section: B Unit Cell Designmentioning
confidence: 99%
“…To determine how many design variables should be included, consider that an arbitrary lossless and reciprocal four-port admittance matrix has a maximum of ten degrees of freedom. However, due to field averaging arguments, the degrees of freedom are reduced to effective material parameters in electrically-small structures, [22], [23]. The beamformer can be viewed as a lossless, reciprocal, polarization conserving medium supporting a TE wave in the x-z plane.…”
Section: B Unit Cell Designmentioning
confidence: 99%
“…Instead of using a pure DL model, surrogate DNNs can also be combined with the above mentioned optimization methods to solve AEM inverse design problems, which we categorically label as a hybrid approach. There are many such reports of hybrid optimization models in the DL AEM literature, [ 14,115,116,119,120,132,135,136,140,141,143,175,176,189,197,208–212 ] which we summarize very generally here while noting that the individual models may vary substantially due to the number of optimization techniques available.…”
Section: Inverse Designmentioning
confidence: 99%
“…[ 218 ] It has been shown that training datasets built with this sampling strategy can yield a substantially more accurate model than one built with a conventional policy (e.g., random selection). Very recently (2020) an uncertainty sampling approach was employed for DNN‐based AEM design, [ 210 ] where the authors report that they were able to reduce the quantity of training data by an order of magnitude compared to random sampling.…”
Section: Open Problems and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The systemically designed dual-λ metalens showed the near-diffraction-limited focusing ability and the intensity distributions Moreover, there is increasing attention on the DL-assisted meta-lens design [84]. A specific example can be found from the Pestourie's report [85], where they presented an active-learning algorithm to reduce at least one order of magnitude of the training time for the surrogate model. The demonstrated ten-layer meta-structure (with 100 unit-cells of period 400 nm) could converge light at three wavelengths (405 nm, 540 nm, and 810 nm) into three different focal spots, respectively.…”
Section: Meta-lensmentioning
confidence: 99%